Tracking of autologous adipose-derived mesenchymal stromal/stem cells after intravenous administration: a pilot study in a dog with induced acute bladder injury - Porato, Mathilde; Antoine, Nadine; Waroux, Olivier; Piret, Joëlle; Noël, Stéphanie; Hamaide, Annick (Frontiers in Veterinary Science, 2025)
IntroductionRegenerative therapy for bladder diseases has been studied in rodent to restore bladder function after a chronic and irreversible bladder wall deterioration. These studies rarely demonstrate the presence of stem cells in the bladder. Cell-tracking after intravenous (IV) administration of stem cells enables to confirm the homing potential of an injury. Our objective was to assess, in one dog, the homing capability of autologous adipose-derived mesenchymal stromal/stem cells (ADMSCs) injected intravenously to an acute bladder injury.MethodsAdipose-derived mesenchymal stromal/stem cells were isolated from the subcutaneous tissue of a dog and labelled. As a homing signal, a full-thickness bladder biopsy representing an acute injury was created in this dog (day 0, control time). Twenty million autologous PKH26-labelled ADMSCs were injected in the cephalic vein on days 1, 4 and 8. Urinalysis was performed (day 5). Bladder biopsy was repeated at the location of the previous scar to assess the presence of labelled ADMSCs in the bladder wall (day 10).ResultsLabelled ADMSCs were observed in the second bladder biopsy, not in the initial biopsy nor in urine. The only adverse event mild, self-limiting hematuria. Complete cell blood count, blood urea nitrogen and plasma creatinine were within normal limits (day 5).ConclusionThe comparison of bladder biopsies before and after IV administration of autologous ADMSCs indicates that they reached the bladder injury. Our protocol was feasible and safe. Hematuria was probably due to the bladder biopsy. These results could encourage the evaluation of this protocol in larger cohorts of dogs.